A instituição de garantias contratuais pela administração pública - Jamaleddine, Adolpho Salim Simonetti (2017)
Current Public Administration contractual activity achieved expressive relevance around the world and, especially in Brazil, categorized as a Democratic Rule of Law, where the Administration is no longer allowed to act exclusively based on authoritarianism. Instead, the enforcement of the public power became a true exception to an Administration consensual acting. At current economic model, in which market specialized itself in production and service offering, the Public Administration, aiming to act efficiently and deliver satisfactory results to citizens, needs to contract with individuals to have access to such goods and services, in order to materialize the public interest. However, given Administration purchasing power, State contractual activity does not only generate contractual effects itself (the attainment of goods and services intended to meet its needs) but also noncontractual effects capable, if properly planned, to be used for the implementation of public policies and intervention on the economic domain. It happens, that Brazilian legal system, mainly due to the payment of public entities judicial debts by a judicial precatory mechanism, plus a high delay on the processment of the demands submitted to the Judiciary, became unable to provide legal security to the Public Administration agreements with private agents. The lack of legal security has implications both from a contractual point of view (higher price paid by Administration when compared with contracts concluded between private agents) and extra contractual aspects (corruption and public resources waste). Given this scenario, from bibliographic and argumentative methods, using exploratory and descriptive literature review, we have analyzed the legality of the use of contractual guarantees by the Public Administration as a tool able to grant legal security to its contracts with the private sector and, as consequence, to provide a better administrative performance to achieve the public interest.